Assessing Occupational Health and Safety Management: A Multi-Center Study of 30 in Primary Health Centers in Indonesia - Siswanto; Fikre, Edilawit (Chakra Brahmanda Lentera Institute, 2025)
Background: Occupational Health and Safety (OHS) is critical in ensuring the protection and well-being of healthcare workers, especially in primary health centres (PHCs) where resource limitations often compromise safety standards. In Indonesia, limited data exists on the overall Performance of OHS management across multiple PHCs. This study aimed to assess the current status of OHS management implementation across 30 PHCs in Tulungagung Regency, Indonesia, focusing on the availability of OHS facilities, staff competency, and their association with OHS management outcomes Methods: A quantitative cross-sectional design was employed involving 30 PHCs selected through simple random sampling. Data were collected using structured questionnaires and checklists assessing facility availability, staff training, and OHS management practices. The OHS implementation instrument consisted of 35 items validated through Pearson correlation (p < 0.05; r > 0.6) and demonstrated good internal consistency (Cronbach’s alpha = 0.762). Descriptive statistics, Chi-square tests, and ordinal logistic regression were used for data analysis. Results: Most PHCs (76.7%) had complete OHS infrastructure, yet 76.7% lacked trained personnel. OHS management Performance was rated as poor in 63.3% of PHCs, moderate in 6.7%, and good in only 30%. A significant relationship was observed between staff OHS competency and OHS management quality (χ² = 7.182; p = 0.028). However, regression analysis indicated that facility availability and staff training accounted for only 8.6% of the variance in OHS management outcomes (Nagelkerke R² = 0.086). Conclusion: Despite sufficient infrastructure in most PHCs, the lack of trained personnel remains a major barrier to effective OHS implementation. These findings highlight the need for targeted capacity-building and systemic approaches that integrate leadership, policy enforcement, and organizational support to improve occupational health outcomes in primary healthcare settings.